KOMUNIKASI INSTRUKSIONAL GURU DALAM PROSES PEMBELAJARAN SISWA DI SEKOLAH DASAR SWASTA (SDS) ALAM DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Siti Ratu Amalia; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Natural Duri Private Primary School (SDS) is a nature-based school. This natural school does not use luxurious buildings but rather wooden stalls, the quality of student education is determined by the quality of the teacher, the method used during the learning process. The teacher's method of applying learning to students with the accelerated learning method, where students learn by involving all the potential that exists in students, then active learning, students are brought to learn in an active and fun way. The concept of the Alam Duri SDS school is based on the Qur'an and Hadith. The education curriculum of SDS Alam Duri which is the basis is that, prioritizing the 4 main points in the basic concepts of education, namely akhlakul karimah, scientific logic, leadership, and entrepreneurship.The purpose of this study was to find out instructional communication methods, media and obstacles during the learning process that the teacher used when teaching.This study used qualitative research methods. Informants from this study were principals, teachers, and students of Alam Duri Elementary School, Mandau District, Bengkalis Regency. While the object of this research is teacher instructional communication in the learning process of students in SDS Alam Duri, Mandau District, Bengkalis Regency. Data collection techniques used are observation, interview and documentation. Data analysis techniques are using interactive model data analysis. In achieving the validity of the data in this study, the authors used an extension of participation and triangulation.The results of the study indicate that instructional communication by the teacher uses problem solving, discussion, practice, and assignment methods. To support instructional communication to run smoothly, learning media is needed. The media used by teachers are visual media such as books, pictures, modules, worksheets, and media that are in nature, laptops, projectors, road boards, and blackboards. Audio visual media, namely using video or film screenings. Meanwhile, instructional communication barriers that occur in the form of psychological obstacles and technical obstacles.Keyword : Instructional Communication, Learning, Learning Process